Prima della piega. La sensibilità delle immagini tra Bergson e Whitehead - Perotto, Francesca (Scenari, 2024)
The article aims to investigate the Deleuzian concepts of image and affect as precursors to the concept of the fold and the problem of individuation, through a comparison with two authors who inspired them. In the case of the image, Bergson; in the case of affect, Whitehead. Although image and affect have been primarily received in an aesthetic sense, their ontological consideration, in relation to the proposals of Bergson and Whitehead, shows their important role in rethinking the problem of subjectivation. This is because image and affect outline a new relationship between subject and experience, overcoming the subject-object dualism and placing expressivity (in the case of the image) and feeling (in the case of affect) at the centre of individuation. Considering image and affect as precursors to the fold also helps to think beyond the criteria of unity and totality, the problem of perspectivism, and the immediate relationship between fold and ethics – also through the role of the negative.